The intersection of translation techniques and ideology in Tangled Ever After subtitles - Iskawati, Inang; Leksananda, Faiz Akbar; Widyasari, Widyasari (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2024)
This research aims to identify and assess the translation strategies and ideologies used by translators in the subtitles of the filmÂ Tangled Ever After. A descriptive qualitative approach focuses on analysing words, phrases, clauses, and sentences that feature translation techniques within the movieâ€™s subtitles. Data collection involves reviewing documents and archives, watching the film, and examining the subtitles in both the source and target languages, followed by transcription. The analysis includes watching the film, reading the subtitles, evaluating the employed translation techniques and ideologies, and drawing conclusions. The findings indicate that 10 distinct translation techniques were used across 24 instances in the subtitles. The techniques employed were: literal translation (5 instances), compensation (4), modulation (3), transposition (3), borrowing (2), amplification (2), description (2), discursive creation (1), generalization (1), and reduction (1). The analysis reveals that the most frequently used technique was literal translation, representing 20.83% of the instances, followed by compensation (16.6%) and modulation and transposition (12.5% each). Techniques such as borrowing, amplification, and description appeared less frequently, while discursive creation, generalization, and reduction were the least utilized, each making up 4.16% of the total.